RANCANGAN SISTEM APLIKASI PELAYANAN PENDUDUK PADA RT.011 RW.03 KELURAHAN GEDONG BERBASIS JAVA NETBEANS - Dio Try Rauffan Rauffan; Sutan Mohammad Arif; Fita Widiyatun (Jurnal JI-Tech, 2021)
Rukun Tetangga (RT) is an organization formed through local community deliberations in the context of serving the population determined by the village government or Lurah. In a population organization, population data collection is very important in order to store important data on the residents living in the RT/RW as an information system and to implement a population service system. However, RT.011 RW.03 Gedong Village still performs population services manually and has not been computerized at all. Then the solution needed to change the method of the population service system RT.011 RW.03 Gedong Village, namely by designing a population service application system that can replace the bookkeeping/archives method into a more computerized system, so that the population services provided become more effective. , fast, conceptualized and up to date. The research method used in this research is using qualitative data collection techniques by observation, interviews, and literature study. In the steps of developing this population service system, researchers use the waterfall development methodology, so that they can determine the problems that occur, collect what data is needed infull, analyze problems that occur with the collected data, design the system, and make reports. end of this research. This resident service application system is designed using the Java Netbeans programming language using MYSQL as the database. To create a system, we need a design so that the system can function as needed. In this design, researchers make DAD (Data Flow Diagram), Normalization, ERD (Entity Relationship Diagram), and display screen population services. With the implementation of computerized population services is one step forward in the application of information technology.